Comments on the type locality, type series, and geographic distribution of Pseudopaludicola falcipes (Hensel, 1867) (Amphibia, Anura) - Langone, José A.; Lavilla, Esteban O.; Sá, Rafael O. De; Cardozo, Darío (Zootaxa, 2015)
The genus Pseudopaludicola was erected by Miranda–Ribeiro, 1926 to accommodate Liuperus falcipes Hensel, 1867a. Currently, there are 18 recognized species of Pseudopaludicola, with 45% of the species described since 2003. Although Pseudopaludicola falcipes is the type species, Hensel’s description lacked designation of type specimens for that species; furthermore, it was based on a series of 30 individuals (without collection numbers or indication of where were they deposited) from "Provinz S[ão]. Pedro do Rio Grande do Sul" (today Rio Grande do Sul State, Brazil).